The first case report of an intraosseous epidermoid cyst in the distal phalanx of the index finger with infection resulting in single clubbing finger: A case report and review of the literature - Alhaskawi, Ahmad; Zhou, Haiying; Dong, Yanzhao; Lai, Jingtian; Wang, Zewei; Hasan Abdullah Ezzi, Sohaib; Goutham Kota, Vishnu; Hasan Abdulla Hasan Abdulla, Mohamed; Sun, Zhenyu; Lu, Hui (Frontiers in Surgery, 2023)
An intraosseous epidermoid cyst at the distal phalanx of the index finger is extremely rare. These cysts are asymptomatic unless they ruptured, severely infected, or transformed into malignant squamous cell carcinoma. We present a case of a single clubbing finger in an adult diagnosed with an intraosseous epidermoid cyst in the distal phalanx of the index finger, with no history of pulmonary or cardiovascular diseases. Preoperative MRI showed an expansile lytic lesion with a sclerotic margin. Histopathological examination indicates a wall of stratified squamous epithelium covered keratinous cell debris, which was the key to the correct diagnosis of an intraosseous epidermoid cyst. Written informed consent was obtained from the patient for publication of this case report and any accompanying images.